Architectural fragments - Dunn, Andrew (Scottish Archaeological Internet Reports, 2001)
A total of 412 separate fragments derived exclusively from the area under excavation; that is they represent remains of buildings which have collapsed in situ and which have since undergone robbing and further reduction. Masons' marks were found on 226 fragments (mostly on fragments of ceiling vault ribbing) and 44 different types were identified.